Identification and Characterization of Genes Involved in Field Pennycress (Thlaspi arvense L.) Glucosinolate Production (nzz047.OR20-06-19). (13th June 2019) - Ringling, Keagan; Chopra, Ratan; Anderson, Nickolas; Marquart, Len; Marks, M David
Abstract: Objectives: Field pennycress ( Thlaspi arvense L. ) is a winter annual oilseed undergoing development as a cash cover crop for the Upper Midwest. While it provides ecosystem benefits when planted between conventional crop rotations, there are few end-uses for wild pennycress. Pennycress is high in oil and protein, and current efforts aim to improve seed composition to generate environmentally sustainable food sources. Similar to Arabidopsis thaliana and oilseed rape, pennycress is rich in glucosinolates, which limits seed palatability and utility. This study aimed to identify mutations responsible for low glucosinolate pennycress lines in a mutant population. Methods: 39 low glucosinolate pennycress lines from a M3 mutant population were identified using brassica-calibrated NIRS and validated using column-exchange chromatography. Lines underwent whole genome sequencing to identify mutations in known brassica orthologs involved in glucosinolate production. We assessed the impact of three mutations on gene expression using RT-qPCR. Results: We identified mutations in three orthologs involved in glucosinolate production. Putative candidates were selected for co-expression validation based on amino acid changes in highly conserved regions of peptide sequences. Genes of interest included the transcription factor bHLH005, the amino acid chain elongation gene IMD1, and the core structure biosynthesis gene CYP83A1. The bHLH005 mutant showed a 48% reduction in sinigrin. Expression decreased in several glucosinolate-related genes including MAM1, AOP2-like, and CYP83A1 by 0.98, 0.82, and 0.78-fold respectively. The IMD1 mutant showed a 45% reduction in sinigrin. Expression decreased in IMD1, MAM1, AOP2-like, and CYP83A1 by 0.77, 0.81, 0.72, and 0.73-fold respectively. The CYP83A1 mutant showed a 19% reduction in sinigrin. Expression decreased in CYP83A1, MAM1, and AOP2-like by 0.14, 0.16, and 0.22-fold respectively. Conclusions: Understanding pennycress glucosinolate production can allow for the development of low-glucosinolate pennycress lines. We identified and validated three genes involved in pennycress glucosinolate production that can be used to develop low glucosinolate pennycress lines. Ultimately, this can improve the economic viability of the pennycress system by providing new end use opportunities. Funding Sources: PepsiCo R&D.